Predictive factors of clinical success after adrenalectomy in primary aldosteronism: A systematic review and meta-analysis - Manosroi, Worapaka; Atthakomol, Pichitchai; Phinyo, Phichayut; Inthaphan, Piti (Frontiers in Endocrinology, 2022)
Unilateral adrenalectomy is the mainstay treatment for unilateral primary aldosteronism (PA). This meta-analysis aimed to systematically analyse predictors of clinical success after unilateral adrenalectomy in PA. A search was performed using PubMed/Medline, Scopus, Embase and Web of Science from their inception to February 2022. Observational studies in adult PA patients which reported predictors of clinical success after unilateral adrenalectomy were included. A random-effects model was employed to pool the fully adjusted odds ratio (OR) or standardized mean difference (SMD) with 95% confidence interval (95% CI). Thirty-two studies involving 5,601 patients were included. Females had a higher clinical success rate (OR 2.81; 95% CI 2.06–3.83). Older patients, patients with a longer duration of hypertension and those taking a higher number of antihypertensive medications had lower clinical success rates (OR 0.97; 95% CI 0.94–0.99, OR 0.92; 95% CI 0.88–0.96 and OR 0.44; 95% CI 0.29–0.67, respectively). Compared to non-clinical success cases, patients with clinical success had a lower body mass index (SMD -0.49 kg/m2; 95% CI -0.58,-0.39), lower systolic (SMD -0.37 mmHg; 95% CI -0.56,-0.18) and diastolic blood pressure (SMD -0.19 mmHg; 95% CI -0.33,-0.06), lower serum potassium (SMD -0.16 mEq/L; 95% CI -0.28,-0.04), higher eGFR (SMD 0.51 mL/min/1.73m2; 95% CI 0.16,0.87), a lower incidence of dyslipidemia (OR 0.29; 95% CI 0.15–0.58) and a lower incidence of diabetes mellitus (OR 0.36; 95% CI 0.22–0.59). Multiple predictors of clinical success after unilateral adrenalectomy in PA were identified which can help improve the quality of care for PA patients.